EFFECT OF FINANCIAL PERFORMANCE ON COMPANY’S VALUE MODERATED BY DIVIDEND POLICY (CASE STUDY: INSURANCE COMPANY AND BANKING COMPANY THAT LISTED IN INDONESIA STOCK EXCHANGE) - Benyamin Eliezer Pascareno (Jurnal Ilmiah Ekonomi Bisnis, 2017)
Company’s value provides a maximum wealth to shareholders when the stock prices rise. The higher the stock price of a company, the higher the wealth of the shareholders. Company’s value is shown by the company’s ability to pay dividends. The amount of dividends may affect the stock price. The company’s ability to pay the dividends is closely related to the company’s ability to make a profit. This study aimed to analyze the effect of liquidity, leverage, profitability on company’s value. In addition, it also aimed to analyze the moderating effect of company’s performance by dividend policy on company’s value. Eighteen companies that listed in Indonesia Stock Exchange during the period 2010-2013, consist of insurance and banking companies, were selected as samples of study. Research variables which included company’s value (Tobin’s Q), liquidity (cash ratio), leverage (debt to equity ratio), profitability (return on equity) and dividend policy (dividend payout ratio) were estimated using standard formulas  from related data available in company’s financial reports and Yahoo Finance website. Data were analyzed using moderating regression analysis. Results of the study showed that liquidity, leverage and profitability partially and simultaneously do not affect the company’s value. Also, after moderated by dividend policy, liquidity, leverage and profitability still do not affect company’s value simultaneously and partially. Keywords: company’s value, company’s performance, dividend policy.